Answer:
b is the answers for the question
Step-by-step explanation:
please mark me as brainlest
M=1-3/-5-4
M=-2/-9
M=2/9
y=2/9x+c
let y=3 and x=-4
3=2/9<span>(-4)+c
3=-8/9+c
3+8/9=c
C=35/9
y=2/9x+35/9
</span>
Answer:
X is equal
Step-by-step explanation:
look at the angle
Answer:
<em>y=-6</em>
Step-by-step explanation:
<em>Geometric Sequences</em>
Any given sequence is said to be geometric if each term
can be obtained as the previous term
by a constant value called the common ratio.
![a_n=a_{n-1}.r](https://tex.z-dn.net/?f=a_n%3Da_%7Bn-1%7D.r)
or equivalently
![a_n=a_1.r^{n-1}](https://tex.z-dn.net/?f=a_n%3Da_1.r%5E%7Bn-1%7D)
Looking closely at the sequence 2, y, 18,-54, 162 we can try to find out if it's a geometric sequence or not. We compute the possible common ratios
and we see they both result -3. If we use r=-3 and try to find the second term (y), then
y=2*(-3)=-6
Now we compute the third term: (-6)(-3)=18
Since we got the third term as given in the original sequence.
So y=-6
The correct answer for the question that is being presented above is this one: "2(x - 1)(3x + 4) = 0."
<span>6x 2 + 2x - 8 = 0
(2x - 2) (3x + 4) = 0
2(x - 1)(3x + 4) = 0
The correct answer for the question that is being presented above is this one: "</span><span>(x - 4)^2 = -19."</span><span>
x2 - 8x + 3 =0
x2 - 8x + 16 = -3 - 16
(x - 4)(x - 4) = -19
(x - 4)^2 = -19</span>